A Comparative Review of 3D Printing Technologies and their Applications: A Systematic Review for Future of Medicine Fabrication - Mustafa, Muhammad Abid; Malik, Aqsa; Javed, Eman; Amjad, Aliza; Iqbal, Sana; Mustafa, Eman; Rasheed, Namra; Shafiq, Aqsa; Fahad, Muhammad; Mughal, Maryam; Jaan, Gohar; Ramzan, Nageen (International Journal of Pharmaceutical Investigation, 2025)
This review explores the role of additive manufacturing, particularly 3D printing, as an innovative approach in targeted drug delivery. It effectively addresses the limitations of traditional methods, such as high costs, complex geometrics and difficulties in individualized medications. The advent of 3D printing offers a modern solution, enabling the manufacturing of customized 3D objects from digital models. The approval of Spritam® (levetiracetam) by the FDA, the first additive manufacturing tablet, is a clear indication of the demand for 3D printing. This technique, which creates products layer-by-layer through a two-step process of data transfer and print head movement in all three dimensions, is gaining popularity. The review explores the diverse additive manufacturing methods applicable to drug delivery systems, including Fused Deposition Modeling (FDM), Stereo Lithography (SLA) and others. FDM, in particular, stands out for its creativity and cost-effectiveness. Beyond drug delivery, additive manufacturing has found applications in tissue engineering, manufacturing of complicated geometries, controlled-release systems and individualized medication for specific patient needs. The technology empowers the creation of intricate, customized structures loaded with drugs, demonstrating great potential for targeted therapies and personalized medicine.
Keywords: Modern Fabrication; Individualized Medicine; Dosage form printing; Nanotechnology; FDA Approved